Identification of the Location, Type, and Causes of Fencers Injuries Based on Discipline - Ulfah, Amalia; Rachman, Aryadi; Erliana, Mita (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This study aims to determine the location, type, and causes of fencers injuries based on discipline. The method used in this research is descriptive quantitative. The results showed that on epee fencers, injuries were often experienced at the location of the lower extremity of the thigh 100%, with the type of bruise injury 85.71% and the cause was from intrinsic factors due to wrong movement techniques 57.14%. On sabre  fancers, injuries are often experienced at the location of the lower extremity of the thigh 57.14%, with bruises, cramps, and abrasions 42.84% each and the cause is from intrinsic factors due to lack of warm-up 71.43%. On foil fencers, injuries are often experienced at the location of the lower extremities of the thighs 66.67%, with the types of bruises and cramps each 66.67% and the cause is from intrinsic factors due to lack of warm-up 50%. the conclusion of this study is that of all fencers, injuries are often experienced, namely at the location of the lower extremities of the thighs with the types of bruises and cramps caused by intrinsic factors, namely lack of warm-up. Degen fancers have a higher risk of injury than sabel and floret.